Engajamentos militantes e construções identitárias na trajetória de Mundinha Araújo - SERRA, Déborah Arruda (2021)
The present dissertation is inscribed in a research agenda that has been developed in the scope of the Laboratory of Studies on Political and Cultural Elites (LEEPOC/UFMA) about the work of agents, enrolled in various social domains, in the formulation of symbolic goods and conceptions about the “culture”, “politics” and “history” of Maranhão. The specific investigation of the work developed here examines the trajectory of Mundinha Araújo, aiming to understand the conditionings of the multinotabilities conquered and the possibilities of administration of strategic identities, acting on the construction of her public image. We highlight, above all, her intellectual investments and militant engagement through her association with the Centro de Cultura Negra do Maranhão (CCN). To this end, we seek to situate her in relation to different conditions and domains of insertion, analyzing her social properties, dispositions, intervention repertoires, cultural investments, forms of identification, among other attributes mobilized and pertinent to Mundinha’s affirmation as a woman “spokesperson” for “black culture” in the state.